Impact of soil scarification on reindeer pastures - Eriksson, Olof; Raunistola, Tuomo (Rangifer, 1990)
During recent years, soil scarification has become a standard procedure for improving seed beds after logging. Around 57 000 ha were treated, primarily through harrowing and ploughing, in the counties of Vâsterbotten and Norbotten during 1985. The positive effects of scarification, from a forestry point of view, are improved access to plant nutrients, raised soil temperatures and reduces surface moisture. The aim of the present study was to describe long-term changes in the ground vegetation following scarification. Harrowing affects 45-55% of the plant cover while ploughing affects 65-90%. 10 years after ploughing and harrowing about 20% of the surface is still without vegetation. Real long-term effects remain in dispute. It has been claimed that ploughing, at least, may lead to irreversible changes.